PENGARUH EFIKASI DIRI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA DENGAN PRESTASI KARIR SEBAGAI VARIABEL MEDIASI PADA PEGAWAI DINAS PANGAN KABUPATEN SUKOHARJO - Bronto Sarono; Sri Isfantin Puji Lestari,; Santosa Tri Prabawa (JURNAL WIRANOMIKA, 2024)
Abstract : The objectives to be achieved in this research are to determine the influence of Self-Efficacy on the Career Achievement of Sukoharjo Regency Food Service Employees, To determine the influence of the Work Environment on the Career Achievement of Sukoharjo Regency Food Service Employees, To determine the influence of Career Achievement on the Work Performance of Sukoharjo Regency Food Service Employees , To determine the influence of Self-Efficacy on the Work Performance of Sukoharjo Regency Food Service Employees, To determine the influence of the Work Environment on the Work Performance of Sukoharjo Regency Food Service Employees, To determine the influence of the Effect of Self-Efficacy on Work Performance with Career Achievement as a mediating variable for Regency Food Service Employees Sukoharjo, To determine the influence of the Work Environment on Job Performance with Career Achievement as a mediating variable for Sukoharjo Regency Food Service Employees. The results of this research are that there is an influence of Self-Efficacy on the Career Achievement of Sukoharjo Regency Food Service Employees. Because the t-value is 1.602 < t-table 1.703, there is no influence of Self-Efficacy on the Career Achievement of Sukoharjo Regency Food Service Employees. There is an influence of the Work Environment on the Career Achievement of Sukoharjo Regency Food Service Employees because the t-count value is 4.762 > t-table 1.703. There is no influence of Career Achievement on the Job Performance of Regency Food Service Employees because the t-calculated value is 0.068 < t-table 1.703. Furthermore, there is no influence of Self-Efficacy on the Job Performance of Sukoharjo Regency Food Service Employees because the t-calculated value is 0.497 < 1.703 with a significant level ( r) 0.619 (not significant), because it is more than 0.05. There is no influence of the Work Environment on the Work Performance of Sukoharjo Regency Food Service Employees because the t-value obtained is 1.387 < 1.703 with a significance level (r) of 0.166 (not significant), because it is more than 0.05. There was no influence of Self-Efficacy on Work Performance with Career Achievement as a mediating variable for Sukoharjo Regency Food Service Employees because the t-value obtained was 0.049 < 1.703 with a significance level (r) of 0.961 (not significant), because it was more than 0.05. Because the t-count value is 0.049 < t-table 1.703, then Career Achievement as a mediating variable is not suitable to use. Self-Efficacy and Work Achievement. There is no influence of the Work Environment on Work Performance with Career Achievement as a mediating variable for Sukoharjo Regency Food Service Employees because the t-value obtained is 0.070 < 1.703.Â Keywords : Self-Efficacy, Work Environment, Job Performance, Career Achievement